Liver regeneration following repeat SBRT - Farach, Andrew; Quesada, Jorge; Teh, Bin S. (Journal of Gastrointestinal Oncology; Vol 6, No 2 (April 13, 2015): Journal of Gastrointestinal Oncology, 2014)
Liver stereotactic body radiation therapy (SBRT) is an emerging treatment option for oligometastases and may confer a survival benefit in select patients. Herein, we document the first case of liver regeneration (LR) following repeat right hepatic lobe SBRT in a woman with breast cancer metastases. Retraction of the treated lobe was significant with a near 50% volume reduction. Compensatory contralateral lobe hypertrophy was noted with a 320% volume increase. The overall liver volume remained stable, within ±5% of baseline. This case indicates that repeat liver SBRT can be delivered safely to individual patients and that compensatory contralateral lobe hypertrophy is observed to maintain a functional liver volume.